Effects of rootstock and soil disinfection on quality of grafted watermelon fruit (Citrullus lanatus L.): a two-year study. Issue 1 (2nd January 2016) - Fallik, Elazar; Alkalai-Tuvia, Sharon; Chalupowicz, Daniel; Zutahy, Yohanan; Zaaroor, Merav; Beniches, Marina; Gamliel, Abraham
ABSTRACT: Grafting is a rapid, effective alternative to the relatively slow methodology of breeding, to provide crop plants with increased tolerance to environmental stress and better yield and quality of fruit vegetables. We evaluated the effect of grafting and soil disinfestation on pre- and postharvest parameters in two consecutive years. In both 2013 and 2014, soil disinfection significantly improved the viability of nongrafted plants compared to the same plants grown in nontreated soil. In both years, plants which were grafted on "Nurit" or "TZ" rootstocks showed significantly better vine vigor, with no evidence of disease in either disinfested or nontreated soil. The yield of marketable watermelon fruit was significantly higher in grafted versus nongrafted plants. Grafting significantly influenced watermelon rind color and flesh color, and strongly influenced taste and texture. Watermelon fruit harvested from plants grafted on "Nurit" were tastier and had better flesh texture than fruit harvested from "TZ"-grafted plants. Disinfection during those two years affected only seed formation. The year factor highly influenced rind color, total soluble solids (TSS) near the rind, TSS at the fruit's heart, taste, and texture. An interaction between grafting and year was found on flesh and TSS near the rind. No grafting × disinfection × year interaction was found.